2009
DOI: 10.1152/jn.90824.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neural Control of Visual Search by Frontal Eye Field: Effects of Unexpected Target Displacement on Visual Selection and Saccade Preparation

Abstract: Murthy A, Ray S, Shorter SM, Schall JD, Thompson KG. Neural control of visual search by frontal eye field: effects of unexpected target displacement on visual selection and saccade preparation. J Neurophysiol 101: 2485-2506, 2009. First published March 4, 2009 doi:10.1152/jn.90824.2008. The dynamics of visual selection and saccade preparation by the frontal eye field was investigated in macaque monkeys performing a search-step task combining the classic double-step saccade task with visual search. Reward was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 105 publications
9
82
0
Order By: Relevance
“…Furthermore, spike rates in the lateral intraparietal area rise like a decision accumulator for a particular saccadic response 78,79 , and microstimulating this area biases responses in a way that is consistent with a shift in the accumulated decision variable 80 . Accumulating activity in frontal eye field motor neurones also predicts motor decisions, as shown recently using a visual search task 81 .…”
Section: Skilled Athletes Are Likely To Have Trained Their Decision Csupporting
confidence: 53%
“…Furthermore, spike rates in the lateral intraparietal area rise like a decision accumulator for a particular saccadic response 78,79 , and microstimulating this area biases responses in a way that is consistent with a shift in the accumulated decision variable 80 . Accumulating activity in frontal eye field motor neurones also predicts motor decisions, as shown recently using a visual search task 81 .…”
Section: Skilled Athletes Are Likely To Have Trained Their Decision Csupporting
confidence: 53%
“…Both the FEF and LIP are strongly associated with target selection (Schall and Thompson, 1999;Schall, 2001;Ipata et al, 2006;Thomas and Paré, 2007). Previous studies have demonstrated a significant degree of independence between visual selection and saccade initiation in the FEF (Thompson et al, 1997;Woodman et al, 2008;Murthy et al, 2009). These authors conclude that variability in SRT is correlated with postvisual/postperceptual processes in the FEF, except when visual processes are taxed by increased targetdistractor similarity (Sato et al, 2001(Sato et al, , 2003.…”
Section: Discussionmentioning
confidence: 94%
“…These no-step-slow and no-step-fast trials were modeled separately. Compensated trials were compared with these latency-matched no-step-slow trials; such latency matching is common practice in neurophysiology (Hanes et al, 1998;Murthy et al, 2009), electrophysiology (Reinhart et al, 2012, and human fMRI (Aron and Poldrack, 2006) studies. Rest (fixation) trials were not explicitly modeled and therefore constituted an implicit baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Using the oculomotor countermanding task, nonhuman primate studies have investigated the cellular basis of reactive inhibition . Computational modeling and neurophysiology studies have also explored rapid modification of saccade plans using the oculomotor search-step task (Camalier et al, 2007;Murthy et al, 2009;Ramakrishnan et al, 2012). Existing neurophysiology and computational modeling work provides an unprecedented basis from which to understand reactive action control in humans.…”
Section: Introductionmentioning
confidence: 99%